Utilizing OpenStreetMap for Collaborative Mobile Reporting System in Irrigation Infrastructure Management - Syaifudin, Yan Watequlis; Saputra, Pramana Yoga; Abdullah, Zaed; Kyaw, Htoo Htoo Sandy; Rahmadani, Alfiandi Aulia; Fatmawati, Triana (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2025)
Irrigation involves the artificial application of water to the soil, crucial to promoting crop growth where rainfall is insufficient, thus supporting healthy plant development and increasing yields. In Indonesia, a large part of the irrigation infrastructure is in disrepair, affecting agricultural productivity and causing food shortages and economic instability, especially among low-income populations. To manage this, local organizations oversee the maintenance of irrigation systems categorized into primary, secondary, and tertiary canals, prioritizing repairs based on severity. Meanwhile, mobile phones have become an essential part of everyday life in Indonesia due to their affordability and utility, which facilitate access to digital resources. Anticipated to reach 97% smartphone penetration by 2029, particularly with Android devices, this technology supports an innovative mobile application strategy for irrigation maintenance. This app enables farmers and community members to report issues collaboratively, accelerating the identification and repair process to improve agricultural management. Complementing this approach, OpenStreetMap (OSM) provides an editable global map resource, continuously updated by users and leveraging tools such as Leaflet JS to offer developers the ability to create interactive and customizable maps, enhancing infrastructure management through community participation. This study introduces a mobile reporting system for managing irrigation infrastructure, integrating several technical components to effectively address maintenance needs. Requiring compatible browsers like Chrome and Safari with specific minimum versions and at least Android 4.0 for accessibility, the system features a public-facing mobile website using OpenStreetMap for mapping. It includes a back-end server that serves mobile and monitoring applications and uses Firebase to store images of irrigation damage while managing database operations with PostgreSQL. The technical setup involves Windows 11, Visual Studio Code, PHP with Laravel for backend operations, and React JS with Leaflet JS for front-end design, running on hardware featuring an Intel Core i5 CPU and NVIDIA GTX 1650 GPU. Key APIs like Get Close Segments, Post Report, and Get The system facilitates data submission with locations and photos, provides report history viewing and filtering, and enhances user engagement through transparency in infrastructure management. The test with local farmers demonstrated the responsiveness and compatibility of the system across various platforms, ensuring that user reports are processed efficiently with reliable admin access for monitoring and tracking.Â Â